A Proposal Based on IoT for Social Inclusion of People with Visual Impairment - Garcia, Cleiton; Fernandes, Patrick; Davet, Patricia; Lopes, João Ladislau; Yamin, Adenauer C.; Geyer, Cláudio Fernando Resin (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
With the wide variety of available mobile devices, of different types, capabilities and technologies, associated with the profusion of wireless communication networks, enables to offer mobile and ubiquitous applications that can be designed to serve blind persons (PCDVs). In this sense, this article has as its principal contribution the approach, called HELIX, proposed to provide accessibility to the visually impaired through the use of concepts of Internet of Things (IoT) in indoor and outdoor environments. The functional architecture of the HELIX is integrated into the adaptation and context recognition subsystem of middleware EXEHDA, which provides support for the acquisition, storage and processing of context information used by the mobile HELIX applications. The applications prototyped were evaluated by the Technology Acceptance Model, and the results were promising.